Thrombosis of Right Spermatic Vein: A Case Report - arvin baranji (Tehran University of Medical Sciences, 2021)
Spermatic vein thrombosis is a rare event that mostly affects the left vein thrombosis but in our report it had developed on the right one that requires meticulous physical examination for diagnosis. The purpose of this case report is to introduce an adult patient with right spermatic vein thrombosis in a 30-year-old man admitted to the operating room for hernia surgery. Spermatic vein thrombosis is an unexpected finding in the differential diagnosis of acute testicular pain.